Labor Market Assimilation and the Self- Employment Decision of Immigrant Entrepreneurs - Magnus Lofstrom (Institute for the Study of Labor (IZA), 1999)
This paper uses data from the 1980 and 1990 U.S. Censuses to study labor market assimilation of self-employed immigrants. Separate earnings functions for the self-employed and wage/salary workers are estimated. To control for endogenous sorting into the sectors, models of the self-employment decision are estimated. Variables for the proportion of immigrants in the population and average earnings ratios are used as instruments to control for self-selection into self-employment and consequently identify the inverse Mills correction term in the earnings models. Self-employed immigrants do substantially better in the labor market than wage/salary immigrants. Earnings of self-employed immigrants are predicted to converge with natives? wage/salary earnings at about age 30 and natives? self-employed earnings at about age 40. Including the self-employed in the sample reduces the immigrantnative earnings gap by, on average, roughly 14 percent.
Keywords: J15; J61; J23; 330; Immigration; assimilation; self-employment; Einwanderung; Migranten; Arbeitsangebot; Selbstständige; Unternehmer; Einkommensverteilung; Soziale Integration; Schätzung; USA